Modelling and evaluation of the hunting behaviour of a high-speed railway vehicle on curved track. (February 2019) - Kumar, Vivek; Rastogi, Vikas; Pathak, PM
Nowadays, rail transport is a very important part of the transportation network for any countries. The demand for high operational speed makes hunting a very common instability problem in railway vehicles. Hunting leads to discomfort and causes physical damage to carriage components, such as wheels, rails, etc. The causes of instability and derailment should be identified and eliminated at the designing stage of a train to ensure its safe operation. In most of the earlier studies on hunting behaviour, a simplified model with a lower degree of freedom were considered, which resulted in incorrect results in some instances. In this study, a complete bond graph model of a railway vehicle with 31 degrees of freedom is presented to determine the response of a high-speed railway vehicle. For this purpose, two wheel–rail contacts grounded on a flange contact and Kalker's linear creep theory are implemented. The model is simulated to observe the effects of suspension elements on the vehicle's critical hunting velocity. It is observed that the critical hunting speed is extremely sensitive to the primary longitudinal and lateral springs. Other primary and secondary springs and dampers also affect the critical speed to some extent. However, the critical hunting velocity is insensitive to vertical suspension elements for both the primary and secondary suspensions. Also, the critical speed is found to be inversely related to the conicity of the wheel.